في بعض الخصائص الفيزيائية للتربة الرملية (Gum acacia) تأثير تركيز الصمغ العربي - شاكر الولي, نهاد; عزيز الموسوي, كوثر (University of Thi-Qar Journal of Science, 2010)
Experiment pot was conducted to study the effect of Arabic Gum ( Gum acacia) as a conditioner by different concentrations on some physical properties of loamy sand soil. This soil treated with five levels of Arabic Gum concentrations were (0.0 , 0.25 , 0.50 , 0.75 and 1.00)% , these concentrations added on the basis of dry soil weight , and wetted to field capacity, afterwards left to dry for 2weeks. The complete Randomize Design (C.R.D) and Revise Least Significant Difference (R.L.S.D) were used to analyze the results.The results showed that the increased concentrations of Arabic Gum increased the agg.>1mm in average (3.07-50.44)% , soil penetration from (53.96-439.16)KN.m-2 , total porosity (33.07-38.21)% and soil moisture (9.67-12.87)% , whereas decreased bulk density from(1.74-1.61)Mg.m-3.